Respuesta medular a la aplicación de polietilenglicol luego del trauma medular agudo experimental en la rata - Blanco, C. (2017)
After the primary mechanical Spinal Cord Injury, there is a complex secondary injury cascade that leads to the progressive death of otherwise potentially viable axons and cells and that impairs endogenous recovery processes. In this paper we discuss the effect of a 1 min application of polyethylene glycol, a hydrophilic polymer and cel fusogen, to a standardized compression injury to the cord. A significative reduction of clinical signs as well as a decrease of histopathological indicators of secondary response to spinal cord trauma. Comparing the results obtained with different control groups. We conclude that the neuroprotective effect of polyethylene glycol applied on the site of the lesion supports the need to prove its systemic effect in animals experimentally injured.\n